Perfil epidemiológico de doadores com sorologia positiva para doença de Chagas crônica em uma rede pública de banco de sangue do Paraná - Villwock, Karen Jiane (2019)
Neglected Tropical Diseases ate defined as a group of 21 diseases caused by infectious agents or parasites. Chagas’ disease is part of this group, being an endemic zoonosis in rural areas of Central and South America. It has a potential risk of transmission through blood and blood products, since most patients in the chronic phase are asymptomatic and unaware of their condition. A qualitative cross-sectional descriptive study was carried out to determinate the sero-epidemiological profile of donors with positive serology for Chagas’ diseases, identified by Centro de Hematologia e Hemoterapia do Paraná (HEMEPAR), between 2013 and 2017. We obtained 1,274 (0.13%) of the 951,965 donations made in the period of the research. Donors with positive seropositivity were predominantly male, aged 26-35 years, with urban domicile and Caucasian ethnicity. The highest prevalences of positive results founded in the North Pioneer of the state, with the Jacarezinho Regional being the first, with 37.1 cases per 10000 donations, followed by the regional ones of Telemaco Borba and Cornélio Procópio. The variables male gender, Caucasian ethnicity, urban dwelling and age group were not consider as explanatory to determine the prevalence of positive cases for chronic Chagas disease serology in 10,000 blood donors. These data will assist in elucidating the frequency of patients with chronic Chagas disease in the state of Paraná, as these are underreported and scarce data, and health policy improvements, instructing physicians and other health professionals to identify and respond more effectively to the needs of these patients.